2015
DOI: 10.3945/jn.114.202754
|View full text |Cite
|
Sign up to set email alerts
|

Wheat Alkylresorcinols Suppress High-Fat, High-Sucrose Diet-Induced Obesity and Glucose Intolerance by Increasing Insulin Sensitivity and Cholesterol Excretion in Male Mice

Abstract: These findings suggest that wheat alkylresorcinols increase glucose tolerance and insulin sensitivity by suppressing hepatic lipid accumulation and intestinal cholesterol absorption, which subsequently suppresses diet-induced obesity in mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
72
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 48 publications
4
72
0
1
Order By: Relevance
“…Wheat fiber has long been known to be effective in controlling body weight and reducing cardiovascular and diabetes risks67819. Recent studies demonstrated that wheat fiber and phytochemicals isolated from wheat bran suppressed body weight gain in high-fat diet fed mice20. In agreement with these reports our results showed that insoluble fibers were more effective in suppressing high-fat diet induced obesity than soluble fibers.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Wheat fiber has long been known to be effective in controlling body weight and reducing cardiovascular and diabetes risks67819. Recent studies demonstrated that wheat fiber and phytochemicals isolated from wheat bran suppressed body weight gain in high-fat diet fed mice20. In agreement with these reports our results showed that insoluble fibers were more effective in suppressing high-fat diet induced obesity than soluble fibers.…”
Section: Discussionsupporting
confidence: 91%
“…This finding is consistent with the result from in vitro test showing that the bamboo shoot fiber has the highest oil-holding capacity compared with cellulose, wheat fiber, and soybean fiber (Supplementary Figure S8). Insoluble hydroxypropyl methylcellulose and wheat fiber were also reported to result in more fecal lipid excretion2022. Our results suggest that inclusion of bamboo shoot fiber resulted in the least metabolizable energy without affecting feeding behavior compared with other fibers.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations